2014
DOI: 10.1016/j.juro.2014.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Evaluation of Orchiectomy Specimens in 51 Late Postpubertal Men with Unilateral Cryptorchidism

Abstract: There was a wide range of histopathological changes in undescended testis. Nearly half the patients may still have significant germ cell activity at a variety of maturation levels. The incidence of intratubular germ cell neoplasia was 2% in this group. Intratubular germ cell neoplasia may be overlooked with hematoxylin and eosin staining so immunohistochemical study should be added for evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…Half of the study population still had significant germ cell activity at different maturation levels. Importantly, the incidence of intratubular germ cell neoplasia was 2% [64].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Half of the study population still had significant germ cell activity at different maturation levels. Importantly, the incidence of intratubular germ cell neoplasia was 2% [64].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[146][147][148][149] In postpubertal men who are subfertile or infertile, the prevalence of GCNIS has been found to range from approximately 1% to 4%, although this depends on selection criteria for biopsy and the population demographics. [150][151][152] Germ cell neoplasia in situ is also associated with microlithiasis (although this finding is nonspecific), 153 which may partially account for the scrotal ultrasound irregularities that are often seen in testes with GCNIS.…”
Section: Epidemiology and Clinical Significance Of Gcnismentioning
confidence: 99%
“…Data of 222 cases with known testicular volume, location and pathology results were evaluated separately from 97 cases with known semen analysis. Mean age of patients was 21.26±0.85 and median age was 21 (19)(20)(21)(22)(23)(24). Mean testicular volume of pathological specimens was 6.90±5.81 cc [median 6 cc (0.1-30)].…”
Section: Resultsmentioning
confidence: 99%
“…Rogers et al [4] detected CIS in only 2 (4%) out of 50 cases, and in another recent study one case of CIS out of 51 patients was found. [22] However it must be kept in mind that about 50% of CIS cases can develop into invasive tumors within 5 years. [6,23,24] In our study, we diagnosed only one patient with seminoma (0.4%) by coincidence On the contrary, a study done in Welvaart-Netherlands concluded that orchiectomy should be performed only after an accurate tumor diagnosis is made since the exact risk of cancerogenesis is unknown.…”
Section: Discussionmentioning
confidence: 99%